Introduction to cyber-warfare a multidisciplinary approach - Shakarian, Paulo (Syngress, 2013)
This book examines the issues related to cyber warfare not only from a computer science perspective but from military, sociological, and scientific perspectives as well.
Includes bibliographical references and index
Keywords: Information warfare -- Case studies; Cyberterrorism; Cyberspace -- Security measures; Computer crimes; Data protection; Guerre de l'information; Études de cas; Cyberterrorisme; Criminalité informatique; Protection de l'information (Informatique); HISTORY; Military; Strategy; Cyberspace; Security measures; Information warfare; information assurance; attribution; Case studies